STRENGTHENING THE HALAL INDUSTRY BASED ON MICRO, SMALL AND MEDIUM ENTERPRISES FOR FOOD PRODUCERS CERTIFIED BY THE INDONESIAN ULAMA COUNCIL IN NORTH SUMATRA PROVINCE - Eko Wahyu Nugrahadi; Khafi Puddin; Nelly Armayanti; Jumiadi AW (CERED Indonesia Institute, 2021)
This study aims to determine the development of the halal industry for SMEs in North Sumatra Province. The test is carried out by factor analysis, namely to find out various factors that can strengthen the development of the halal industry. The factors in question are the role of the government, awareness of MSME actors, sharia compliance. Based on the results of the analysis, all factors determine the strengthening of the halal industry with a significant loading factor. The sample in this study were 45 SMEs spread across the cities of Medan, Binjai and Deli Serdang. The sampling technique used purposive sampling method with criteria for business age above 5 years, average monthly sales above 50 million and already having MUI halal certification. The contribution of this research shows that micro, small and medium enterprises to the regional economy. Local governments play a role in the development of the halal industry. The limitation of this study is that it does not include regulatory variables so that local governments need to issue regional regulations that regulate business/industry actors to always maintain the quality of their products according to Islamic law which is marked by certification from Indonesian Ulama. Board. Further research can add other relevant variables